The influence of posture variation on electromyographic signals in females obtained during maximum voluntary isometric contractions: A shoulder example - Maciukiewicz, J. M.; Lulic, T.; MacKay, K. L.; Meszaros, K. A.; Dickson, C. R. (Journal of Electromyography and Kinesiology, 2022)
Surface electromyography (sEMG) is commonly used to estimate muscle demands in occupational tasks. To allow for comparisons, sEMG amplitude is normalized to muscle specific maximum voluntary contractions (MVCs) performed in a standardized set of postures. However, maximal sEMG amplitude in shoulder muscles is highly dependent on arm posture and therefore, normalizing task related muscular activity to standard MVCs may lead to misinterpretation of task specific muscular demands. Therefore, the purpose of this study was to investigate differences in commonly monitored shoulder muscles using normalized sEMG amplitude between maximal exertions at different hand locations and across force exertion directions relative to standard MVCs. sEMG was recorded from the middle deltoid, pectoralis major sternal head, infraspinatus, latissimus dorsi, and upper trapezius. Participants completed standardized muscle-specific MVCs and two maximal exertions in 5 hand locations (low left, low right, high left, high right, and central) in each of the four force directions (push, pull, up, and down). Peak sEMG was analyzed in the direction(s) that elicited the highest signal for each muscle. All muscles differed by location (p<0.05). Latissimus dorsi had the greatest activation during pulls (32-135% MVC); upper trapezius and middle deltoid while exerting upwards (73-103% and 42-78% MVC, respectively); infraspinatus while pushing (38-79% MVC); and pectoralis major activation was the highest during downwards exertions (48-84% MVC). Normalization of location specific maximal exertions to standard muscle specific MVCs underestimated maximal activity across 90% of the tasks in all shoulder muscles tested, except for latissimus dorsi where amplitudes were overestimated in low right hand location. Normalization of location specific muscle activity to standard muscle specific MVCs often underestimates muscle activity in task performance and is cautioned against if the goal is to accurately estimate muscle demands.